Flowering Periods, Seed Yield Components, Seed Quality, and Patterns of Seed Shattering in Paspalum: Effect of Taxonomy and Nitrogen Fertilization - Chamorro, Luis Leandro (2024)
Perennial warm-season grasses typically have reduced seed yield, making it essential to identify the critical seed yield components. An induced increase in nitrogen could help determine which components are most limiting. This research aimed to estimate seed yield components in Paspalum; evaluate N fertilization effects on the reproductive phase, seed yield components, and seed quality; and establish the pattern of seed shattering over time. Nine genotypes covering different reproductive periods were used. The experimental design was a randomized complete block design in a split-plot arrangement with three replications. The main plots had two nitrogen levels (0 and 150 Kg N ha−1), and the sub-plots contained different genotypes. Seed yield variation was mainly related to reproductive tiller density among germplasm with different flowering periods. Early-flowering germplasm showed an extended flowering period (159%), greater tiller density (27.7%), greater reproductive tiller density (157%), and higher yield (302%) in response to nitrogen fertilization. Seed-quality traits and seed retention were not affected by nitrogen fertilization. Seed retention over time followed an inverted sigmoid pattern, though there was considerable variation among taxonomic groups. Early-flowering germplasm exhibited superior seed retention. Seed yield in Paspalum is mainly influenced by the density of reproductive tillers and seed retention.